84 COVID-19 and Associations with Frailty and Multimorbidity: A Prospective Analysis of UK Biobank Participants. (16th March 2021) - Woolford, S J; D'Angelo, S; Curtis, E M; Parsons, C M; Ward, K A; Dennison, E M; Patel, H P; Cooper, C; Harvey, N C
Abstract: Introduction: Frailty and multimorbidity have been suggested as risk factors for severe COVID-19 disease. We therefore investigated whether frailty and multimorbidity were associated with risk of hospitalisation with COVID-19 in the UK Biobank. Method 502, 640 participants aged 40–69 years at baseline (54–79 years at COVID-19 testing) were recruited across UK 2006–10. A modified assessment of frailty using Fried's classification was generated from baseline data. COVID-19 test results (England) were available 16/03/2020–01/06/2020, mostly taken in hospital settings. Logistic regression was used to discern associations between frailty, multimorbidity and COVID-19 diagnoses, adjusting for sex, age, BMI, ethnicity, education, smoking and number of comorbidity groupings, comparing COVID-19 positive, COVID-19 negative and non-tested groups. Results: 4, 510 participants were tested for COVID-19 (positive = 1, 326, negative = 3, 184). 497, 996 participants were not tested. Compared to the non-tested group, after adjustment, COVID-19 positive participants were more likely to be frail (OR = 1.4 [95%CI = 1.1, 1.8]), report slow walking speed (OR = 1.3 [1.1, 1.6]), report two or more falls in the past year (OR = 1.3 [1.0, 1.5]) and be multimorbid (≥4 comorbidity groupings vs 0–1: OR = 1.9 [1.5, 2.3]). However, similar strength of associations were apparent when comparing COVID-19 negative and non-tested groups. Furthermore, frailty and multimorbidity were not associated with COVID-19 diagnoses, when comparing COVID-19 positive and COVID-19 negative participants. Conclusions: Frailty and multimorbidity do not appear to aid risk stratification, in terms of a positive versus negative results of COVID-19 testing. Investigation of the prognostic value of these markers for adverse clinical sequelae following COVID-19 disease is urgently needed.